2011
DOI: 10.1590/s1677-54492011000200007
|View full text |Cite
|
Sign up to set email alerts
|

Association of lipids with coronary heart disease in a saudi population

Abstract: BACKGROUND: The Saudi population is known to have an unhealthy diet in addition to physical inactivity. OBJECTIVE: To investigate the lipid-mediated risk factors that might be associated with increased incidence of coronary heart diseasein the Saudi population as this was found in Western populations. MATERIALS AND METHODS: Two hundred and twenty subjects suspected of having coronary heart disease underwent coronary angiography and blood draw following a 12-hour fast. Total and HDL cholesterol, triglycerides, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…A varying spectrum of the coronary lesions was noted. The prevalence was similar to another study conducted in Riyadh, Saudi Arabia that suggested 20% of their sample had coronary heart disease [ 16 ]. The occurrence of the acute coronary syndrome spectrum was low, less than 2%.…”
Section: Discussionsupporting
confidence: 86%
“…A varying spectrum of the coronary lesions was noted. The prevalence was similar to another study conducted in Riyadh, Saudi Arabia that suggested 20% of their sample had coronary heart disease [ 16 ]. The occurrence of the acute coronary syndrome spectrum was low, less than 2%.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, the results of the Framingham Heart Study showed that CHD is associated with total cholesterol in subjects aged <50 years, but not in subjects aged 50 years. (30) According to Utami et al, (11) theoretically there should be a correlation between carbohydrate intake and lipid profile. Carbohydrate intake and TC concentration are influenced by the confounding factor of physical activity.…”
Section: Discussionmentioning
confidence: 99%